Physical modeling of development adjustment mechanism for heterogeneous thick oil reservoir - Chen, Xu; Zhang, Zubo; Liu, Qingjie; Sun, Linghui; Xiao, Hanmin; Gao, Jian; Kang, Hao (Frontiers in Energy Research, 2023)
With the gradually deep development of oil field, the remaining oil in reservoir become more scattered, to exploit them within the high water-cut pay become extremely difficult. Based on the characteristics of extremely high water-cut reservoir, three large scale physical models with different injection-production well patterns are designed. Through the analysis of oil production rate and the data of Computed Tomography (CT) scanning, the change law of fluid content within the core are obtained; The new calculation method of sweep efficiency for waterflooding within non-homogeneous models are set up in accordance with the CT number at different waterflooding stages. Furthermore, the development results of different plans are compared with each other, both injection and production with horizontal wells at low-permeability formation have the best recovery, because the displacement fluid can reach the places in reservoir where conventional waterflooding cannot. Therefore, this well pattern is the optimum plan for the positive rhythm model in this experiment, and the development strategy optimization is realized for high water-cut thick oil formation.